Role of bone scan index in the prognosis and effects of therapy on prostate cancer with bone metastasis: Study design and rationale for the multicenter Prostatic Cancer Registry of Standard Hormonal and Chemotherapy Using Bone Scan Index (PROSTAT‐BSI) study. (6th April 2018) - Nakajima, Kenichi; Kaneko, Go; Takahashi, Satoru; Matsuyama, Hideyasu; Shiina, Hiroaki; Ichikawa, Tomohiko; Horikoshi, Hiroyuki; Hashine, Katsuyoshi; Sugiyama, Yutaka; Miyao, Takeshi; Kamiyama, Manabu; Harada, Kenichi; et al.
Abstract : Objective: To present the study design and rationale of Prostatic Cancer Registry of Standard Hormonal and Chemotherapy Using Bone Scan Index, a prospective study aiming to determine the role of the bone scan index, the amount of bone metastasis, in the treatment and prognosis of prostate cancer patients. Methods: A total of 237 patients were recruited at 30 hospitals in Japan. All had prostate cancer with bone metastasis and were scheduled to undergo either hormonal therapy (group H) or chemotherapy (group C). Bone scans were carried out with 99m Tc‐methylenediphosphonate. Follow‐up studies are planned to continue for 3 years, and changes in biochemical and tumor markers in response to hormonal therapy and chemotherapy will be recorded in addition to skeletal‐related events, recurrence, disease progression and death. Results: The basic characteristics of the patients ( n = 200) at the time of registration during December 2016 were as follows: mean age 71 ± 8 years; median bone scan index calculated on‐site 1.9% (range 0.02–13.3%); median number of hot spots 18 (range 1–128); median prostate‐specific antigen 155 ng/mL (range 0.04–22 412 ng/mL); and the most frequent Gleason score 9 (47%). The prostate‐specific antigen value was higher in group H than group C (288 vs 33 ng/mL, P < 0.0001), whereas bone scan indexes were comparable (1.7 vs 2.3%, not significant) between the two groups. Liver metastasis was more frequent in group C than group H (6.1% vs 0.8%, P = 0.035). Conclusions: The baseline characteristics of the Prostatic Cancer Registry of Standard Hormonal and Chemotherapy Using Bone Scan Index database have been established. This collaborative study can now proceed with clarifying the role of the bone scan index for patient management including treatment strategies and prognosis.